The awareness and knowledge of Diploma in Public Administration students about the Novel Influenza A, H1N1 / Muhamad Amirul Azlan, Khairul Akmal Rosly and Farah Fatin Mazlan - Azlan, Muhammad Amirul; Rosly, Khairul Akmal; Mazlan, Farah Fatin (2010)
The topic for our research were “The Awareness and Knowledge of Diploma in Public Administration (DPA) Students About The Novel Influenza A, H1N1”. Our main purpose is to measure the level of awareness and knowledge among students of Diploma in Public Administration for the latest disease, Novel Influenza A, H1N1. For the Chapter 1, its includes an introduction for our research, problem statement, objectives, scope of study, hypothesis, significance, and also the limitation of our project paper studies. In other words, in Chapter 1, we will discuss about an overall introduction for our research in which we will focus on this research. In Chapter 2, it only focus on the Literature Review. In Literature Review, it includes an introduction, the differences between swine flu and bird flu, a history on Novel Influenza A, H1N1 in Malaysia, importance for students awareness and knowledge on H1N1, and also the suggestion on how to prevent novel influenza A, H1N1 before, during and after the infections. This section will elaborate the information of Influenza A, H1N1 from wide to smaller scopes. Chapter 3 talks about the Research Design and Methodology. There are research design, the data collecting methods and sampling procedure and methods of data analysis. How our research been conducted as questionnaire, the methods such as primary and secondary data and our sampling which is students of DPA on every part of study. The design on questionnaire also been include in this chapter. Chapter 4 is about the data analysis and finding which collected from the questionnaire been given before. The questionnaire has been conducted for 150 students of DPA from every part of studies. However, only 126 questionnaire has been collected as a finding. There are total of 21 question been ask to the students. An explanation show on by tables but the pie chart are places on the appendices.